Implementasi Kaidah al-‘Ādah Muhakkamah pada Hak Waris Anak Perempuan Sasak: Implementation of the Rules of al-'Ādah Muhakkamah on the Inheritance Rights of Sasak Girls - Rosmita, Rosmita; Nurfiah, Nurfiah; Mareta Fatmawati (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to determine and understand the implementation of the al-'Ādah muhakkamah principle on the inheritance rights of Sasak daughters. The formulation of the problem is: first, what is the form of inheritance distribution for Sasak daughters. Second, how is the implementation of the al-'Ādah muhakkamah principle in determining the inheritance rights of Sasak daughters. This study uses a qualitative research type, namely library research, which focuses on the study of manuscripts and texts, using normative and comparative approaches. The results of the study found: first, the form of inheritance rights obtained by Sasak daughters is in the form of household furniture, jewelry, clothing and woven fabrics. As for inheritance rights in the form of land, houses and rice fields are fully given to sons, because in the distribution of inheritance in the Sasak community, sons are given more priority, because the Sasak community uses a patrilineal kinship system that draws male lineage. The second is related to the implementation of the al-'Ādah muhakkamh principle, if seen from the implementation process, it is determined through deliberation accompanied by traditional leaders in order to maintain family harmony. However, the inheritance rights determined for Sasak girls are not in accordance with Islamic law values ​​where the level cannot be measured, only determined in the form of household furniture, jewelry, clothing and woven fabrics. Al-'Ādah in the Sasak community cannot be used as law because it is a fāsid custom